A note on an Ancylomenes (Crustacea: Decapoda: Pontoniinae) from the Siboga expedition - Bruce, A. J. (Zootaxa, 2011)
A major landmark in the taxonomy of the shrimps of the subfamily Pontoniinae was the publication of the Siboga Expedition monograph by Holthuis (1952). In this report Holthuis referred four lots of specimens to Periclimenes aesopius (Bate). This species is now placed in the genus Ancylomenes Okuno & Bruce (2010) as Ancylomenes aesopius (Bate, 1863) and is known only from Australian waters (South Australia and Western Australia). Through the kindness of Dr Dirk Platvoet it has been possible to re-examine these Siboga specimens. Re-examination showed that none can now be referred to Bate’s species which is distinguished from all other species of the genus by the presence of three or four post-orbital teeth on the anterior carapace (Bruce, 1977). Several species of Ancylomenes are represented in the Siboga material and Holthuis’s description of the material does not appear based on any specimen in particular. One specimen is however, readily distinguishable from the others by the unusually slender ambulatory dactyli. It is also distinct from all presently known species of Ancylomenes, and is herein designated as a new species and its characters described and illustrated.